Russell, Naomi. A ghost on the path. - Jarvis, Dale Gilbert, 1971- (2011)
Recording of a ghost story told by Naomi Russell, a Grade 7 student at St. Michael's Regional High. The story follows the pattern of traditional Newfoundland stories of tokens or supernatural warnings of death. In the tale, a young man from North River who plays music for dances is walking home from a dance. He meets up with the figure of a girl he knows on the path, but she does not answer him. When he returns home, his mother informs him that the young woman he saw on the path had just been killed in an automobile accident.